Optimizing the Role of Youth Organizations (Karang Taruna) in Empowering Youth Through a Sustainable Governance System in Barru Regency - Herman H; Nurfitraeny Nasruddin; Khusnul Hatimah; Restu Mayang Sara Nur; Dewi D (Yayasan Daarul Huda Kruengmane, 2026)
This community service activity is entitled